Potential of inoculant and phosphorus application on soybean production in Mozambique - Engoke, C.; Boahen, S. (Horizon Research Publishing Co., Ltd., 2018)
Inoculation with effective Bradyrhizobium spp., and phosphorus application enhance atmospheric nitrogen fixation in soybean production. Soybean form symbiotic associations with the right rhizobium strain to incorporate atmospheric nitrogen into the plant tissues. The objective of this study was to evaluate responses of two soybean varieties to inoculation, phosphorus and starter-nitrogen, and their interactions on nodulation, growth, yield components and grain yield in different agroecologies of Mozambique. The study was conducted at three locations in Nampula, Tete and Zambézia provinces in Mozambique during 2012 and 2013 seasons. Two soybean genotypes (Storm and TGx 1904-6F) in split-plot design with phosphorus (P2O5) rates as main plot, inoculation application as subplots and nitrogen rates as sub-sub plots with four replications were used. Nodulation, plant growth, biomass nutrient content at R3 stage, yield and yield components were evaluated. Data analyzed for combined and individual locations in Statistical Analysis System® 9.4 indicated that inoculation increased nodulation and yield (37% to 95%) in both soybean genotypes but the effect of phosphorus on nodule formation was not consistent across sites and varieties. Inoculants have a potential to supply required nitrogen for soybean production in Mozambique because farmers seldom use mineral fertilizers due to its high cost.